English and Arabic Vowels: Ferreting Out the Similarity for Bridging Pronunciation Accuracy - Rosalin Ismayoeng Gusdian; Riski Lestiono (Yayasan Visi Intan Permata, 2021)
This study aimed at exploring the similarity between Arabic and English vowel sounds that may benefit Indonesians to pronounce some English vowels. This investigation approached whether their Arabic acquisition could facilitate their learning target language, which is English. To come up with the sought-after similarities, requiring an in-depth study on the existing literatures discussing the phonetic features of those two languages was the step to take. Accordingly, an archival study was selected and employed as a qualitative research design supported by the secondary data analysis method. Several kinds of literatures as the data sources were comprising scholarly journal articles, theory books of Arabic and English phonology, and proceedings. All of the data were available online and were readily accessed through several search-engine platforms; one of which was Google Scholar. The data collection process involved identifying the data set, evaluating the data set, tabulating, and synthesizing the data. The findings have articulated that English and Arabic languages have lax/short and tensed/long vowels. The short vowels comprised /ʌ/; /ɪ/; and /ʊ/. Meanwhile, the long vowels encompassed /a:/, /i:/, and /u:/. This sort of similarity has conveyed the notion of linguistic proximity, which contributes to language transfers upon acquiring the target language.